Pengaruh Mckenzie Cervical Exercise terhadap Nyeri Leher Pekerja Home Industry Tahu - Octavia Nurhidayanti; Elis Hartati; Prita Adisty Handayani (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Occupational health problems in the home industry are found in many work-related diseases and unsafe workplace conditions, one of the diseases arising from work is musculoskeletal complaints. Mckenzie cervical exercise can reduce neck pain however it has not been proven for home industry workers. This study aims to determine the effect of Mckenzie cervical exercise on the scale of neck pain on workers in tofu home industry. Methods: This research design used pre-experimental design with one-group pre-posttest design. The number of samples were 30 respondents with a total sampling technique. The instrument was the Numeric Rating Scale and data were collected using interview techniques. Results: Workers with neck pain in the “tahu” home industry were provided Mckenzie cervical exercise. The statistical test used was the dependent t-test. The results showed that Mckenzie cervical exercise is effective in reducing the scale of neck pain with a p-value of 0.000. Conclusion: The recommendations of this study are for routine workers to perform Mckenzie cervical exercise therapy in each implementation in order to help reduce the scale of neck pain in tofu home industry workers